ANALISIS KECERDASAN EKOLOGIS SISWA SEKOLAH DASAR DI SD NEGERI 147 PEKANBARU (STUDI DI KELAS TINGGI SD NEGERI 147 PEKANBARU) - Tri Rusmiyati; Eddy Noviana; Zufriady Zufriady (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2019)
Ecological intelligence is an ability or competence that a person has in adapting to the circumstances of the surrounding environment and can apply it in daily life. In this study, researchers conducted research on how ecological intelligence in elementary school students in the high class in terms of skills. Ecological intelligence in terms of skills includes the skills of using and utilizing resources, living in harmony with environmental preservation, solving environmental problems, and skills in environmental responsibility. This type of research is quantitative descriptive research, the main data source (primary data) obtained from questionnaires given to respondents and the results of interviews and documentation which is support data (secondary data). The results of this study show that the ecological intelligence of elementary school students in high class is classified as skilled (89.89%). When viewed from each indicator, the ecological intelligence of elementary school students in the high class is also categorized as skilled. This proves that elementary school students in the high class have begun to understand how important it is to protect the environment and also students already care about the surrounding environment.